Diet quality and its associated factors among community dwelling older adults in urban district in Kuala Lumpur, Malaysia - Nohan, Amin Faiz; Adznam, Siti Nur ‘Asyura; Jamaluddin, Rosita; Norazman, Camilla Wahida (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Diet quality is an essential factor in determining the adherence towards dietary guidelines. This study aims to assess the diet quality among community-dwelling older adults and identify the factors associated with the diet quality. Method: This is a cross-sectional study, conducted among 138 community-dwelling older adults living in PPR flats, Kuala Lumpur. Subjects were randomly recruited in this study. Diet Quality Index (DQI) was used to identify diet quality index of elderly. The Chi-square Test of Independence and Pearson’s correlation test were used to determine the association between tested covariates with DQI. Results: Majority of the respondents were reported with good diet quality (74.6%), whereas quarter of them (25.6%) had poor diet quality. Significant difference between the diet quality and the adherence on the food groups were observed for all food groups (p <0.05). Conclusion: The results of this study provide a new insight on the diet quality of the elderly with good and poor diet quality. More inclusion of factors that are related to the diet quality needs to be emphasized in future studies among older adults as it would play a beneficiary component in improving their nutritional status.